The Opinions of Students that Study in the Primary Education Social Studies Teaching Programme (Candidate Teachers) about the Teaching of Human Rights and Democracy Course - (:unkn) unknown (MARMARA UNIV, 2016)
The purpose of this study is to acquire contributive findings related to Human Rights and Democracy course by applying to opinions of students, determine problems and present what should be done for an efficient course. In this study, it is focused on the concepts of human rights and democracy, the relationship between these concepts and education and how an efficient Human Rights and Democracy course is carried out. In this study, scanning model and cross-sectional design are carried out. The centre of the study consists of teacher candidates of third class students of Social Studies, Faculty of Education, from Inonu University, 19 Mayis and Firat Universities. The sample of this study consists of 214 students that take place in this area. Findings have been acquired as a result of examining sources that are related to the subject matter and the survey that has been prepared by the researcher and carried on students. The survey that consists of 27 questions, a kind of attendance Likert, has been carried out. Acquired data have been analyzed. Some suggestions have been presented according to the results of the study.
Keywords: Human rights; democracy education; teaching